Analisis Konten Strategi Marketing Mix Beauty Influencer dalam Mempromosikan Brand The Originote: Studi Kasus Akun Tiktok @Laurasiburian - Tiurmaida, Patricia; Vitryanov, Nuansa; Tasya, Pebia (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
In the development of technology, product marketing varies, one of which uses influencers as an effective marketing strategy for a brand with its own image and characteristics, giving a big impact on consumers. Therefore, this research analyzes the 4P marketing mix strategy used by beauty influencer Laura Siburian in promoting The Originote beauty brand through her TikTok account. Descriptive qualitative method is used to analyze Laura Siburian’s content in reviewing The Originote cushion products, focusing on the aspects of price and product quality. Laura Siburian successfully promoted the product through the TikTok digital platform by providing information about suitable face types, prices, and product quality. Promotion is carried out for The Originote’s new product, the Cushion with 12 shades, and purchases can be made through the TokoPedia marketplace platform. The results of this study provide insight into the effectiveness of marketing strategies used by beauty influencers in promoting beauty products through social media.